DESIGN AND DEVELOPMENT OF A POWER QUALITY MONITORING AND AUTOMATION SYSTEM USING CAPACITOR BANK FOR SMALL-SCALE INDUSTRY - Sirait, Deny Nazarius Sirait (Jurnal Informatika dan Teknik Elektro Terapan, 2025)
Low power factor in small-scale industries results in energy inefficiency, increased power consumption, and higher operational costs. To address this issue, this study proposes a monitoring and automatic power factor correction system utilizing a capacitor bank controlled according to load demand. The system is built using an ESP32 microcontroller as the main controller, integrated with a PZEM-004T sensor for voltage and current measurements, and a 25 A Solid State Relay (SSR) for capacitor switching. Monitoring is facilitated through a mobile application developed using MIT App Inventor. The research methodology involves hardware and software design, system implementation, and performance evaluation. Experimental results demonstrate an improvement in power factor from 0.72 to 0.99, a reduction in apparent power from 2.18 kVA to 1.60 kVA, and a decrease in reactive power from 1.50 kVAR to 0.24 kVAR. The current draw was reduced from 10 A to 7.34 A, yielding estimated energy savings of 139.2 kWh or approximately IDR 201,102.24 per month. Sensor accuracy testing shows an average error of 0.40% for voltage and 1.13% for current. The proposed system enables small industries to enhance energy efficiency, reduce operational expenses, and monitor power quality via smartphone.